THE EFFECT OF USING PICTURE-CUED STORYTELLING TECHNIQUE ON THE SPEAKING ABILITY OF THE THIRD YEAR STUDENTS OF SMPN 8 - Aulia Andhini; Dahnilsyah Dahnilsyah; Marzuki Marzuki (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research was aimed to find out whether or not there was a significant effect using Picture-Cued Storytelling Technique on the speaking ability of the third year students of SMPN 8 Pekanbaru. The research design was a re-experimental research with one group pre-test and post-test design. The sample was class IX-3 chosen by using cluster random sampling technique. In order to collect the data, a pre-test and post-test were administered and then the data were statistically analyzed by using the t-test formula. The result showed that the mean score of the post-test was higher than the mean score of the pre-test (51.43>47.39). The value of t-test was 11.528 while the value of t-table in significance level 5% df = 32 was 2.037. Therefore, Alternative Hypothesis (Ha) was accepted and Null Hypothesis (H0) was rejected. It could be concluded that there was a significant effect of using Picture-Cued Storytelling Technique on the speaking ability of the third year students of SMPN 8 Pekanbaru.Key Words: Picture-Cued Storytelling Technique, Speaking Ability